Level of Patient Satisfaction in Griya Antapani Public Health Center, Bandung City 2022 - Destiani, Irna; Rejeki, Yunita Fitri; Laelasari, Laelasari (LPPM STIKes Muhammadiyah Ciamis, 2023)
One indicator of the success of health services is patient satisfaction. Puskesmas as health service providers, if the patient feels dissatisfied the patient will be disappointed and will create a public perception about the image of the puskesmas that cannot provide good service. The purpose of the study was to determine the level of patient satisfaction in health services at the Griya Antapani Public Health Center, Bandung City. The research method used is quantitative with an observational descriptive type of design. The number of samples obtained at the time of data collection from August 23 to 27, 2022 was 33 patients with accidental sampling technique. Data analysis used univariate analysis by describing the frequency distribution. The results showed that the level of patient satisfaction in health services at the Griya Antapani Public Health Center was obtained as many as 5 people (15.2%) said they were quite satisfied, and 28 people (84.4%) said they were satisfied. customers.